2000
DOI: 10.1515/jpem.2000.13.7.933
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Mineral Metabolism in Children Receiving Carbamazepine and Valproic Acid

Abstract: Dual energy X-ray absorptiometry (DXA) was used to assess lumbar spine (L2-4) and femoral neck bone mineral density (BMD) in 36 children taking either carbamazepine or valproic acid for longer than one year, for generalized idiopathic epilepsy. Patients were matched with controls. Biochemical parameters of bone mineral metabolism were also measured. BMD values at both the femur neck and lumbar spine in both the carbamazepine and valproic acid groups were not significantly different from that of the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 10 publications
2
39
2
1
Order By: Relevance
“…The initial search yielded 1603 research reports, of which 228 were excluded due to identical title or authors; 1056 were excluded due to ineligible study design (including non-human studies, review articles, case reports, comment, letter, experimental study, and/or fractureonly outcome). After full-text screening, 22 studies were included (Chung and Ahn, 1994;Baer et al, 1997;Akin et al, 1998;Kafali et al, 1999;Erbayat Altay et al, 2000;Verrotti et al, 2002;Voudris et al, 2002;Ecevit et al, 2004;Oner et al, 2004;Babayigit et al, 2006;Kumandas et al, 2006;Nicolaidou et al, 2006;El-Hajj Fuleihan et al, 2008;Nettekoven et al, 2008;Gniatkowska-Nowakowska, 2010;Rauchenzauner et al, 2010;Babacan et al, 2012;Dimić et al, 2013;Razazizan et al, 2013;Turan et al, 2014). Table 1 summarizes the characteristics of the included studies published between 1994 and 2014.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial search yielded 1603 research reports, of which 228 were excluded due to identical title or authors; 1056 were excluded due to ineligible study design (including non-human studies, review articles, case reports, comment, letter, experimental study, and/or fractureonly outcome). After full-text screening, 22 studies were included (Chung and Ahn, 1994;Baer et al, 1997;Akin et al, 1998;Kafali et al, 1999;Erbayat Altay et al, 2000;Verrotti et al, 2002;Voudris et al, 2002;Ecevit et al, 2004;Oner et al, 2004;Babayigit et al, 2006;Kumandas et al, 2006;Nicolaidou et al, 2006;El-Hajj Fuleihan et al, 2008;Nettekoven et al, 2008;Gniatkowska-Nowakowska, 2010;Rauchenzauner et al, 2010;Babacan et al, 2012;Dimić et al, 2013;Razazizan et al, 2013;Turan et al, 2014). Table 1 summarizes the characteristics of the included studies published between 1994 and 2014.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…A total of 11 studies comprising 23 datasets, which included 645 subjects and 579 controls, evaluated the effect of AEDs on lumbar spine BMD (Chung and Ahn, 1994;Akin et al, 1998;Kafali et al, 1999;Erbayat Altay et al, 2000;Oner et al, 2004;Babayigit et al, 2006;Kumandas et al, 2006;El-Hajj Fuleihan et al, 2008;Gniatkowska-Nowakowska, 2010;Babacan et al, 2012;Dimić et al, 2013) The changes in BMD of trochanter and femoral neck were assessed by three datasets from two studies (Oner et al, 2004;Ecevit et al, 2004) . Sensitivity analysis showed that no single study affected the summary estimates significantly.…”
Section: Pooled Effect Of Aed Treatment On Bmdmentioning
confidence: 99%
“…Most of the available studies on AEDs and BMD have addressed the use of carbamazepine ( Table 1). None of the studies have shown a decrease in BMD or BMC in the total body, lumbar spine, hip or forearm [40][41][42][43][44][45]. Children were selected in good physical condition and did not have concomitant diseases (i.e., no influence from malnutrition or vitamin D deficiency could be expected) ( Table 1).…”
Section: Carbamazepinementioning
confidence: 99%
“…In contrast to carbamazepine, the results for valproate have been more diverse. Two studies, both from Turkey, in children aged 8 -12 years found no decrease in spine BMD [40,42] with the use of valproate. The first study had a duration of > 1 year [40], and the second ∼ 3 years [42].…”
Section: Valproatementioning
confidence: 99%
“…[35] у пациентов, при-нимающих ВК, показано значительное повышение уровня щелочной фосфатазы (ALP) по сравнению с контрольной группой, однако в работе E. Erbayat Altay и соавт. [48] про-демонстрирован уровень остеокальцина на верхней грани-це нормы. Несмотря на то что ВК может снижать МПК с изменением биохимических маркеров костной ткани, в работе J. Elliott и соавт.…”
Section: традиционные пэпunclassified